1990
DOI: 10.1182/blood.v75.9.1801.bloodjournal7591801
|View full text |Cite
|
Sign up to set email alerts
|

Human endothelial cells synthesize, process, and secrete fibronectin molecules bearing an alternatively spliced type III homology (ED1)

Abstract: Cellular fibronectin (Fn) bearing an alternatively spliced extra type III structural repeat (ED1) is normally present at low concentrations in blood plasma. The source of this material remains uncertain. In this study, primary cultures of human umbilical vein endothelial cells (HUVEC) labeled with 35S-methionine were observed to synthesize Fn monomers both with and without this segment. Monomers isolated from cell lysates with antibodies to the ED1 sequence comigrated in nonreduced sodium dodecyl sulfate polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The anti‐human EIIIA mAb 3E2 (17, 20) and mAb IST‐9 (24) were obtained from Sigma and from Sera Lab (Crowley Down, UK), respectively. Anti‐EIIIA mAb 15/27 and mAb 52/54, derived from sister hybridomas, were purified on protein A–Sepharose (25, 26). The mAb 52/54 was coupled to preactivated Sepharose 4B according to the manufacturer's instructions (Amersham Pharmacia, Piscataway, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…The anti‐human EIIIA mAb 3E2 (17, 20) and mAb IST‐9 (24) were obtained from Sigma and from Sera Lab (Crowley Down, UK), respectively. Anti‐EIIIA mAb 15/27 and mAb 52/54, derived from sister hybridomas, were purified on protein A–Sepharose (25, 26). The mAb 52/54 was coupled to preactivated Sepharose 4B according to the manufacturer's instructions (Amersham Pharmacia, Piscataway, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…These findings include altered endothelial procoagulant expression, 36 increased concentration of the endothelial pressor, endothelin, [37][38][39][40][41][42][43][44][45][46] increased adhesion molecules [47][48][49] in the circulation, and direct markers of endothelial activation. [50][51][52][53][54][55][56][57][58][59][60][61] Most importantly, several of these markers are increased weeks to months before evident preeclampsia. 35,[62][63][64] On the basis of these findings, the concept that many of the pathophysiological changes of preeclampsia are initiated by altered endothelial function seems reasonable ( Fig.…”
Section: Markers Of Endothelial Activation In Preeclampsiamentioning
confidence: 99%
“…In vitro studies have demonstrated that in addition to being incorporated into extracellular matrix, a soluble form of ED-A cFN is secreted into the medium, potentially reflecting intravascular release of this protein by human endothelial cells in vivo. 92 Cellular fibronectin plays a central role in the adhesion, morphology, and migration of endothelial cells. While it is a major component of the endothelial extracellular matrix, cFN is normally only a minor component of circulating fibronectin and thus is an accurate marker of endothelial cell injury.…”
Section: Endothelial Cell Adhesion Moleculesmentioning
confidence: 99%